Child development - Berk, Laura E. (Boston : Allyn & Bacon Pearson, 2009)
Provides a clear and coherent understanding of the sequence and underlying processes of child development, emphasizing the interrelatedness of all domains of development - physical, cognitive, emotional, and social. This sixth edition presents classic and emerging theories in an engaging writing style.
Includes bibliographical references and index.
Keywords: Child development; Child psychology